Frequency response and bandwidth analysis of multi‐layer graphene nanoribbon and multi‐walled carbon nanotube interconnects. (1st September 2014) - Majumder, Manoj Kumar; Kukkam, Narasimha Reddy; Kaushik, Brajesh Kumar
Abstract : This reported research analyses and compares the bandwidth and absolute frequency response of a multi‐layer graphene nanoribbon (MLGNR) and a multi‐walled carbon nanotube (MWCNT) at local, semi‐global and global interconnect lengths. The transfer function of the driver‐interconnect‐load system is obtained by representing the interconnect line with an equivalent single conductor model of either a MLGNR or a MWCNT. Using absolute frequency response, it is observed that the bandwidth of the MLGNR is higher by almost ten times and four times in comparison to the MWCNT for local and global interconnect lengths, respectively.